Randomized controlled study of the histamine H3 inverse agonist MK-0249 in adult attention-deficit/hyperactivity disorder - Herring, W Joseph; Wilens, Timothy E; Adler, Lenard A; Baranak, Christine; Liu, Kenneth; Snavely, Duane B; Lines, Christopher R; Michelson, David (The journal of clinical psychiatry, 2012)
It has been suggested that the histamine subtype 3 receptor inverse agonists such as MK-0249 might be effective in treating attention-deficit/hyperactivity disorder (ADHD). We evaluated the effects of MK-0249 in adults with ADHD. A randomized, double-blind, placebo-controlled, incomplete block, 2-period crossover study of MK-0249 5-10 mg/d and osmotic-release oral system (OROS) methylphenidate 54-72 mg/d (active comparator) was performed in 72 men and women aged ≥ 18 to ≤ 55 years who met DSM-IV criteria for ADHD of either inattentive or combined subtype and who had a chronic course of behavior disorder. The study was conducted from August 2007 through April 2008 at 6 US sites. Primary efficacy was assessed by the mean change from baseline in the Adult ADHD Investigator Symptom Rating Scale (AISRS) total score after 4 weeks of treatment. Change from baseline in AISRS at week 4 for MK-0249 was not different from placebo (P = .341), whereas a significant benefit was seen for OROS methylphenidate versus placebo (P < .001). Analysis of secondary end points, including the Conners Adult ADHD Rating Scales, showed results consistent with the AISRS. A similar percentage of patients reported adverse events for MK-0249 compared with placebo (73% versus 69%, respectively). However, a greater percentage of patients reported insomnia as an adverse event with MK-0249 treatment compared with placebo (32% versus 11%, respectively). MK-0249 10 mg/d is not effective for the treatment of adult ADHD. ClinicalTrials.gov identifier: NCT00475735.